Lemma exchange in a microcontroller based parallel SAT solver - Schubert, T.; Becker, B. (IEEE Computer Society Annual Symposium on VLSI: New Frontiers in VLSI Design (ISVLSI'05), 2005)
We present a new and more powerful variant of our distributed SAT procedure for microchip PIC microcontrollers. The algorithm is an adaption of the state-of-the-art solver CHAFF optimised for the limited resources of the microchip processors. It contains features of modern SAT engines like conflict-driven learning and nonchronological backtracking as well as an efficient work stealing method to run several processors in parallel. The underlying hardware environment is a special multiprocessor system based on a PC ISA slot card holding up to 9 PIC microcontrollers. Thereby the communication topology between the computing units can be reconfigured during runtime. In this work we focus on what is sometimes called lemma exchange in the literature: the possibility to exchange useful information (conflict clauses / lemmas) between processors working on different parts of the search tree of the same problem instance. Besides technical aspects we also analyse the speedup obtained by lemma exchange and describe the effects observed during our experiments.